Pemanfaatan Briket Sekam Padi Sebagai Penghasil Panas Pada Kompor Generator Termoelektrik Untuk Penerangan Pedagang Kaki Lima - suliono suliono; Emin Haris; Rachmatullah Rachmatullah; Abu Rizal Al Gifari (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
Street vendors or traders who sell on the side of the road or who sell in city parks have lighting problems, because lighting is very influential on visitors or buyers. For areas close to people's homes, traders distribute lamps from one of the residents to turn on the lights by paying Rp.5,000. This study aims to help street vendors overcome the problem of lighting using alternative electric energy based on Thermoelectric Generator (TEG) type TEC-12706 with the side using fire generated by rice husk briquettes while the cold side using a 12V DC fan. This study uses several variations to light the lamp effectively and efficiently, including: variations in the number of cooling fans (without fans, 1 fan and 2 fans), variations of the peltier series (series, parallel and combination), variations in the number of peltiers (3 peltier and 6 peltier ). Based on the test results on the Thermoelectric Generator (TEG) the highest temprature difference is produced using 1 fan with 131.4 ℃, a circuit with 3 peltiers that produces the highest voltage, current and power using a series circuit with 6.84V, 0.28A, and 1.92W, and which is able to turn on a 12V 5 Watt DC lamp using 6 peltier to produce 13.5V, 0.55A, and 7,425W. So that with six peltier can turn on one fan and one 5 watt DC lamp.